Energy harvesting system for kenaf fibre reinforced epoxy composite vertical wind turbine blade - Ariffin, Ahmad Hamdan (2015)
The usage of wind energy as a form of renewable energy is becoming increasingly popular year by year. The performance of wind turbine systems depends upon factors such as design, aerodynamic performance and material selection. Thus, Structural Health Monitoring (SHM) has become crucial in evaluating the performance of wind turbines in real time. Furthermore, the application of smart material in SHM systems can be utilised as a micro energy harvester as well. Nonetheless, the application of SHM in Malaysia's climate for wind turbines is still premature, especially in the use of biocomposite material in its blade system. Hence, the objectives of this research can be summarised as follows: to assess the the effect of bonding technique of Macro Fiber Composite (MFC) system in a kenaf composite fibre and incorporated for micro energy harvester in wind turbine blade. A feasibility investigation of bonding MFC techniques and fabrication process optimisation were conducted. The mechanical properties of woven and random chopped kenaf were investigated, especially with regards to flexural and tensile strength. A modal testing experiment was conducted on the kenaf plate to assess the correlation factors involved in the vibrating structure, including natural frequency. A plate vibration test was performed on the kenaf plate to analyse the factors influencing the performance of the micro energy harvester. A thorough analysis of the bonding MFC technique was also performed on the kenaf composite turbine blade. The experiment was conducted on a tested laboratory vertical axis wind turbine for micro energy harvesting. Further statistical analysis via the Taguchi method was applied on the plate and the turbine blade. It was found that the embedded MFC was capable of inducing electricity and a signal. In mechanical properties analysis, the properties of woven kenaf composite improved up to 199% and 177%, as compared to random chopped kenaf, for flexural strength and tensile strength respectively. The bonding type and resonance of particular structure factors show significant influence on the performance of the micro energy harvester via Taguchi analysis in plate vibration test. Bonded MFC on the surface shows a 348% increment compared to embedded MFC in turbine blade micro energy harvesting analysis. Projection performance of functional VAWT shows that additional percentage, from 26% up to 107%, energy harvested from the wind turbine system for bonded MFC. Finally, energy harvested kenaf composite turbine blade was developed successfully.